Towards a spectral library of Roman to Early Christian Cypriot floor mosaics - Lysandrou, Vasiliki; Cerra, Daniele; Agapiou, Athos; Charalambous, Eleftherios; Hadjimitsis, Diofantos G. (My University, 2017)
Floor mosaics are of great interest for archaeologists and art historians. While in the last decade other scientific sectors supported their study mainly from a technical point of view, through traditional archaeometric analysis, this paper suggests an innovative methodological approach and presents some preliminary results aiming to a non-destructive investigation based on the spectroradiometric analysis of stones used for manufacturing the ancient floor mosaics of Cyprus. This method evaluates the results of spectroradiometric analysis in relation to reliable destructive analysis completed in the past on the hereunder examined samples. In addition, the results of the proposed approach foresee to contribute to the expansion of the existing Cypriot database of floor mosaics, improving their characterization by collecting their spectral signatures in the range of 350–2500 nm. The proposed methodology has been applied to a number of stone samples directly linked to pavement floor mosaic tesserae from Cyprus. The results have shown that spectroradiometers may be used in order to identify mineralogical compositions of the stones with an accuracy of nearly 90%. To the best of our knowledge, this is the first time that a comprehensive spectral library related to Cyprus floor mosaics is derived.
Keywords: Cyprus; Discrimination analysis; Floor mosaics; Roman; Spectral library; Spectral signature